IDENTIFYING LEARNING OUTCOMES IN STUDENTS’ PARAGRAPH WRITING - Kappa, Eyleen; Usman, Sriati; Agussatriana, Agussatriana; Rofiqoh, Rofiqoh (e-Journal of ELTS (English Language Teaching Society), 2023)
The purpose of this research is to know the students’ learning outcomes in writing paragraphs. There are five indicators in writing descriptive paragraphs: content, organization, vocabulary, grammar, and mechanics. Its subjects were eighth grade students of SMP Negeri 2 Ampibabo. From a total population of 80 students, 25 students were selected as the sample of the research. This research applied descriptive research design. In collecting data, the researcher gave a test of writing descriptive paragraphs to the students to find out their ability of students in writing paragraphs. In this case, the highest score of 25 students in the class, was 95 which is considered an excellent level. The lowest result gets a score of 40 which is considered the fair level. Thus, generally, the students’ mean score of writing ability particularly in writing paragraphs was 63.2 and it was considered a good level of ability. Thus, from the data presentation, it can be concluded that the learning outcomes in the writing paragraph of the eighth grade students of SMP Negeri 2 Ampibabo were at a good level.